Inactivated influenza vaccine effectiveness and an analysis of repeated vaccination for children during the 2016/17 season. Issue 37 (5th September 2018) - Shinjoh, Masayoshi; Sugaya, Norio; Yamaguchi, Yoshio; Iibuchi, Noriko; Kamimaki, Isamu; Goto, Anna; Kobayashi, Hisato; Kobayashi, Yasuaki; Shibata, Meiwa; Tamaoka, Satoshi; Nakata, Yuji; Narabayashi, Atsushi; et al.
Highlights: Vaccine was effective in preventing illness, 38% against influenza A (mostly H3N2). Vaccine was effective in preventing illness, 39% against influenza B. Infants showed no significant vaccine effectiveness. The children who were immunized in two consecutive seasons were more likely to have influenza. However, the influenza vaccine should be recommended every season for children. Abstract: Objectives: We assessed the vaccine effectiveness (VE) of inactivated influenza vaccine (IIV) in children 6 months to 15 years of age during the 2016/17 season. In addition, we estimated the impact of repeated vaccination in children on VE. Methods: Our study for VEs in preventing influenza and admission due to influenza were conducted according to a test-negative case-control design (TNCC) based on influenza rapid diagnostic test results. We also analyzed the VE by vaccine status in the current and previous seasons for the impact of repeated vaccination. Results: During the 2016/17 season, the quadrivalent IIV was used in Japan. The adjusted VE in preventing influenza illness was 38% (95% CI, 29–46) against influenza A and 39% (95% CI, 18–54) against influenza B. Infants showed no significant VE. The VE in preventing hospitalization was not demonstrated. For the analysis of repeated vaccination, the vaccine was effective only when immunization occurred in the current season. The children who were immunized in two consecutive seasons were more likely to develop influenza compared to those immunized in the current season only (odds ratio, 1.58 [95% CI, 1.05–2.38], adjusted odds ratio, 1.53 [95% CI, 0.99–2.35]). However, the odds ratio of repeated vaccination was not significant when the analysis excluded those who developed influenza in the previous season. Conclusions: VE in children in the 2016/17 season was similar to values previously reported. Repeated vaccination interfered with the VE against any influenza infection in the 2016/17 season. The results of our study suggest that decreased VE by repeat vaccination phenomenon was associated with immunity by influenza infection in the previous season. However, the influenza vaccine should be recommended every season for children.